Pengaruh Penerapan Akuntansi Berbasis Akrual terhadap Transparansi Keuangan: Studi Kasus Pemerintah Daerah di Indonesia - Intan Dwi Lestari; Lismita Maharani; Sandra; Peny Cahaya Azwari (PT. Pustaka Cendekia Publisher, 2025)
Transparency in financial management serves as a crucial cornerstone for establishing an accountable and trustworthy government. To enhance the quality of public sector financial reports, the Indonesian government has adopted an accrual-based accounting system in accordance with Government Regulation Number 71 of 2010, which outlines Government Accounting Standards. This study seeks to assess how the implementation of accrual-based accounting influences the level of financial transparency in local governments. Utilizing a quantitative approach based on case studies of 20 local governments, data were collected through questionnaires and documentation analysis. The findings reveal that accrual-based accounting significantly enhances the transparency of local financial practices reports, by producing more complete, relevant, and publicly accessible information. However, its implementation still faces various challenges, such as limited human, resource capacity, suboptimal technological infrastructure, and lack of commitment from local leaders. Therefore, the success of implementing accrual accounting requires ongoing efforts to strengthen institutional capacity and build a culture of transparent and accountable governance.